Epidemics and Pandemics: What Lessons from History? - Philippe, Clairay (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
Intrinsically linked to human existence, viruses have accompanied and marked the different stages of the development of civilization. Today, confronted with a new "enemy", the Covid-19, our societies seemed once again dumbfounded by this challenge before they reacted. This article will try to recall, through a historical approach, how much the great global epidemics and pandemics have shaped our world, and to show that often, from a societal point of view, the same stages are repeated.